1983
DOI: 10.1029/jc088ic12p07519
|View full text |Cite
|
Sign up to set email alerts
|

The “insulating” effect of a steep continental slope

Abstract: Geochemical evidence shows that the midcontinental slope off the Mid‐Atlantic Bight constitutes an important sink for substances attached to fine particles. It is reasonable to infer that near‐bottom currents in this region are generally much weaker than those over the adjacent continental shelf, allowing the settling out of fine particles and their incorporation into permanent sediment. A partial dynamical explanation of this phenomenon may be sought in the “insulating” effect of a steep slope. At levels belo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 26 publications
(18 reference statements)
0
20
0
Order By: Relevance
“…The MAB circulation has been extensively studied through observations and modeling Beardsley and Boicourt 1981;Chapman 1986;Csanady and Hamilton 1988;Linder and Gawarkiewicz 1998;Flagg et al 2006;Lentz 2008a). Depth-averaged mean currents are predominantly along isobath directed equatorward, with speeds of 0.03-0.1 m s 21 that increase with distance offshore (Lentz 2008a(Lentz , 2010.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The MAB circulation has been extensively studied through observations and modeling Beardsley and Boicourt 1981;Chapman 1986;Csanady and Hamilton 1988;Linder and Gawarkiewicz 1998;Flagg et al 2006;Lentz 2008a). Depth-averaged mean currents are predominantly along isobath directed equatorward, with speeds of 0.03-0.1 m s 21 that increase with distance offshore (Lentz 2008a(Lentz , 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Lentz (2008a) discussed the possibility of other types of forcing, but the hypothesis that ASPG exists seems reasonable. The Gulf Stream (GS) and Slope Sea gyre (Csanady and Hamilton 1988) may drive an ASPG at the shelf break, but the penetration of the pressure field onto the shelf is limited (Wang 1982;Csanady and Shaw 1983;Chapman 1986). The Gulf Stream (GS) and Slope Sea gyre (Csanady and Hamilton 1988) may drive an ASPG at the shelf break, but the penetration of the pressure field onto the shelf is limited (Wang 1982;Csanady and Shaw 1983;Chapman 1986).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At these low frequencies, the extent of influence of the imposed pressure is inversely proportional to the slope of the sea bottom [Chapman and Brink, 1987]. Thus, the steep topography of the WFE "insulates" the WFS from the influence of the LC pressure and turns the along-break north-tosouth pressure drop into a sharp drop in pressure onshore, giving rise to a focussed southward flow along the shelf edge and leaving the flow weak over the rest of the shelf [Csanady and Shaw, 1983]. …”
Section: Introductionmentioning
confidence: 99%
“…Csanady and Shaw (1983) have suggested that because of the relatively weak currents on the slope, this region may be a sink for fine-grained particles. Because anthropogenic pollutants often adhere to fine-grained particles, over long periods of time the slope may be a region of accumulation for these contaminants.…”
Section: Introductionmentioning
confidence: 99%